2016
DOI: 10.1074/jbc.m116.717751
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor-CXCR4 Receptor Interactions

Abstract: An emerging number of non-chemokine mediators are found to bind to classical chemokine receptors and to elicit critical biological responses. Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine that exhibits chemokine-like activities through non-cognate interactions with the chemokine receptors CXCR2 and CXCR4, in addition to activating the type II receptor CD74. Activation of the MIF-CXCR2 and -CXCR4 axes promotes leukocyte recruitment, mediating the exacerbating role of MIF in atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 88 publications
(127 reference statements)
2
86
0
Order By: Relevance
“…CXCR4 also binds macrophage migration inhibitory factor (MIF), a cytokine involved in the regulation of innate immunity ( 18 ). MIF binds to the N-terminal tail of CXCR4 and to the exterior side of TM helices, but not inside the TM pocket ( 18 , 19 ). MIF also binds to other receptors, including CXCR2, CD74/CD44, and ACKR3 ( 20 ), which complicates the dissection of its activities.…”
Section: Cxcr4 and Its Ligandsmentioning
confidence: 99%
“…CXCR4 also binds macrophage migration inhibitory factor (MIF), a cytokine involved in the regulation of innate immunity ( 18 ). MIF binds to the N-terminal tail of CXCR4 and to the exterior side of TM helices, but not inside the TM pocket ( 18 , 19 ). MIF also binds to other receptors, including CXCR2, CD74/CD44, and ACKR3 ( 20 ), which complicates the dissection of its activities.…”
Section: Cxcr4 and Its Ligandsmentioning
confidence: 99%
“…In addition to Ii/CD74, three G protein-coupled receptors of the CXC chemokine family have been identified as receptors for MIF: CXCR2, CXCR4 and, most recently, CXCR7, which has also been termed atypical chemokine receptor 3 (ACKR-3) [23,25,26,27,91,92]. Although MIF is not related to chemokines, it has been shown to contain sites that are similar to the N-terminal region and the N-loop segment of chemokines.…”
Section: Invariant Chain As Receptor For Migration Inhibitory Factmentioning
confidence: 99%
“…Furthermore, the binding site 2 on the chemokine receptors includes a transmembrane cavity that is occupied by the unstructured N-terminal regions of chemokines in the course of binding, a process important for receptor activation. With MIF, however, no such interactions have been detected, suggesting a mechanism of receptor activation that differs from chemokines [92]. The chemokine receptors may not only compete with Ii in binding of MIF, but they may also function as co-receptors for Ii because CXCR2 and CXCR4 have been shown to form complexes with Ii/CD74 by co-immunoprecipitation [23,25].…”
Section: Invariant Chain As Receptor For Migration Inhibitory Factmentioning
confidence: 99%
“…In agreement with our previous results, the functional analysis revealed cellular movement among the most represented and upregulated function (activation z-score of 1.797, p = 1.97 × 10 −3 ) ( Table 1). Importantly, we have also evidenced that the most upregulated gene associated with AnaR-CM treatment was represented by CXCR4 (2.7 fold, p = 4.53 × 10 −21 ), a well-known receptor involved in regulating cell movement [53][54][55][56].…”
Section: Anar Cells Affect Motility Of Macrophage Through An Increasementioning
confidence: 71%
“…This is in line with evidence showing the multifaceted role of CXCR4 on regulating motility of different cell lines, including immune cells. Indeed, CXCR4 is expressed by leukocytes, macrophages, and hematopoietic stem/progenitor cells, and its signaling pathway may affect their chemiotaxis function [53][54][55][56]. It has been also demonstrated that during obesity, CXCR4 is involved in macrophage recruitment to the adipose tissue [61].…”
Section: Discussionmentioning
confidence: 99%